Proceedings. 'Meeting the Tests of Time'., International Test Conference
DOI: 10.1109/test.1989.82278
|View full text |Cite
|
Sign up to set email alerts
|

A new framework for analyzing test generation and diagnosis algorithms for wiring interconnects

Abstract: Increasing complexity of circuit boards and surface mount technology has made it difficult to test them using traditional in-circuit test techniques. A design-forAtestability framework has been proposed as the IEEE Standard 1149.1, Test Access Port and Boundary-Scan Architecture. This architecture simplifies board test by providing an electronic bed of nails. It also provides access to other test features that may be present on a chip.Because of the serial nature of the tests that use BoundaryScan, it is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(40 citation statements)
references
References 3 publications
0
39
0
1
Order By: Relevance
“…Rodríguez-Montañés et al [14] proposed a diagnosis approach based on the relative values of voltages induced by interconnect opens and incorporating I DDQ data. Further literature is available on testing open defects in board interconnects which is not a target of our work [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez-Montañés et al [14] proposed a diagnosis approach based on the relative values of voltages induced by interconnect opens and incorporating I DDQ data. Further literature is available on testing open defects in board interconnects which is not a target of our work [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous work in testing interconnects focused on the development of deterministic tests for interconnect between chips at the board level [7,9,15,17,22,25,28]. As pointed out above, the extension of these board level methods to backplane testing is non-trivial.…”
Section: Introductionmentioning
confidence: 99%
“…It has applications to design and testing of very large scale integration (VLSI), multi-chip module (MCM) and printed circuit board (PCB) systems [2,3,4,5,8]. A wiring network consists of a set of nets, each having one driver and one receiver.…”
mentioning
confidence: 99%
“…Garey, Johnson and So [3] observed that if we are given partial information about the edge set of G, then finding an optimal algorithm to test G = K n becomes NP-complete (reduction from chromatic number). For our problem of finding all connection classes, Jarwala and Yau [4] provided a heuristic using lg n + n − k queries, where k is the number of components. There is also a non-adaptive version of the problem where the inputs of all queries are decided before asking the oracle any question [2,8,9].…”
mentioning
confidence: 99%